1992
DOI: 10.1002/chin.199208011
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Crystallographic Site Discrimination in Aluminophosphate Molecular Sieves by Solid‐State NMR: Influence of the Field‐Dependent Isotropic Second‐Order Quadrupolar Shift on High‐Resolution 27Al DOR NMR.

Abstract: 1992 magnetic resonance, nuclear quadrupole resonance magnetic resonance, nuclear quadrupole resonance (solids and liquids) D 6560 -011Crystallographic Site Discrimination in Aluminophosphate Molecular Sieves by Solid-State NMR: Influence of the Field-Dependent Isotropic Second-Order Quadrupolar Shift on High-Resolution 27Al DOR NMR. -The low-field 27Al double-rotation NMR results obtained for the very large pore aluminophosphate VPI-5 confirm the recently reported crystal structure refinement (based on a symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Using 27 Al double-rotation (DOR) NMR, previous studies have shown that the line at 40 ppm is actually composed of two overlapping resonances from 4-coordinated Al in a 1:1 intensity ratio allowing their differentiation in the MAS spectrum at a lower magnetic field strength . The 2D 27 Al MQ-MAS NMR spectrum of AlPO 4 -54· x H 2 O, exhibits two distinct sites of 4-fold (around 40 ppm) and one site of 6-fold (around −15 ppm) 27 Al.…”
Section: Resultsmentioning
confidence: 99%
“…Using 27 Al double-rotation (DOR) NMR, previous studies have shown that the line at 40 ppm is actually composed of two overlapping resonances from 4-coordinated Al in a 1:1 intensity ratio allowing their differentiation in the MAS spectrum at a lower magnetic field strength . The 2D 27 Al MQ-MAS NMR spectrum of AlPO 4 -54· x H 2 O, exhibits two distinct sites of 4-fold (around 40 ppm) and one site of 6-fold (around −15 ppm) 27 Al.…”
Section: Resultsmentioning
confidence: 99%